The Effectiveness of Giving Sutarma Nutritious Drink "Date Tarap Milk" on Increasing Upper Arm Circumference of Pregnant Women - Ika Yulianti; Maria Ulfanti Uhle Lewuk; Ririn Ariyanti; Doris Noviani; Idha Farahdiba (Indonesian Journal of Global Health Research, 2024)
Chronic Energy Deficiency (CED/ kekurangan energi kronik / KEK) must be overcome by increasing adequate nutrient intake. The additional nutritional intake that can be provided is by utilizing local wisdom from Kalimantan, namely tarap fruit seeds which have nutritional content such as protein, carbohydrates, fats, and vitamins combined with dates in an innovation "SUTARMA". The purpose of this study is to find out the benefits of giving Sutarma nutritious drink "Date Tarap Milk" can increase the upper arm circumference (lingkar lengan atas/LILA) in pregnant women at the Karang Rejo Health Center. This research method is a quasi-experimental quantitative research with a one-group pretest posttest design. The research sample used was 15 pregnant women. This research was conducted in the work area of the Karang Rejo Health Center. This study provides Sutarma intervention for 15 days with a frequency of 1 time a day. And based on descriptive analysis, the average value of the LILA pre-test before the administration of Sutarma to pregnant women was 21.7 cm and the post-test of LILA after the administration of Sutarma for 15 days was 23.1 cm, and the average increase in LILA in mothers was 1.3 cm. Based on the statistical test using paired samples t-test in the output table of t-test results, a significant value of p-value is obtained. 0.000, which means that the p-value < 0.05. Thus, Ho was rejected and H1 was accepted. Thus, it can be concluded that the administration of Sutarma's nutrient-dense drink "Susu Tarap Kurma" is effective and significant in increasing LILA in pregnant women at the Karang Rejo Health Center.